2014
DOI: 10.1371/journal.pone.0113287
|View full text |Cite
|
Sign up to set email alerts
|

Whole Genome Association Mapping of Plant Height in Winter Wheat (Triticum aestivum L.)

Abstract: The genetic architecture of plant height was investigated in a set of 358 recent European winter wheat varieties plus 14 spring wheat varieties based on field data in eight environments. Genotyping of diagnostic markers revealed the Rht-D1b mutant allele in 58% of the investigated varieties, while the Rht-B1b mutant was only present in 7% of the varieties. Rht-D1 was significantly associated with plant height by using a mixed linear model and employing a kinship matrix to correct for population stratification.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
104
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(125 citation statements)
references
References 75 publications
17
104
0
Order By: Relevance
“…Numerous studies exhibited that there were major QTL/genes on chromosome 2DS, such as the well-known and widely used dwarf gene Rht8 (Chebotar et al 2013; Griffiths et al 2012; Zanke et al 2014). Recently, using a fine-resolution mapping approach, the Rht8 genetic interval has been reduced from 20.5 to 1.29 cM, flanking by DG279 and DG371 (Gasperini et al 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies exhibited that there were major QTL/genes on chromosome 2DS, such as the well-known and widely used dwarf gene Rht8 (Chebotar et al 2013; Griffiths et al 2012; Zanke et al 2014). Recently, using a fine-resolution mapping approach, the Rht8 genetic interval has been reduced from 20.5 to 1.29 cM, flanking by DG279 and DG371 (Gasperini et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Over the past two decades, the successful application of quantitative–genetic methodology has facilitated identification of numerous QTL for PHT in wheat (Borner et al 2002; Cadalen et al 1998; Wurschum et al 2015, 2017; Yu et al 2014; Zanke et al 2014). In our recent study, two QTL ( QPht.cau - 2D.1 and QPht.cau - 2D.2 ) for PHT linked in coupling phase were mapped on the short arm of chromosome 2D (Zhai et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Several MTAs for agronomic traits were detected, including new loci. We identified several MTAs for PH, a trait of renowned complexity in wheat (Maccaferri et al ., ; Zanke et al ., ). At FDR 5%, we identified MTAs on Chr 1B (19.4 and 23.2 cM), 2A (154.6 cM), 3B (166 cM), 4A (114.6 cM), 4B (14.4 cM), 6B (71.9 and 155.1 cM) and 7B (92 cM).…”
Section: Discussionmentioning
confidence: 97%
“…The map position reported for GA20ox1 and KAO‐B1 makes them candidates for our MTA on Chr 4A. Rht13 co‐localizes with the MTA on Chr 7B (Zanke et al ., ). It should be noted that the majority of studies conducted up to now have focused on bread wheat, and that durum wheat might show a different composition for these complex traits.…”
Section: Discussionmentioning
confidence: 97%
“…In the SD population, the two additional QTL on 4AL and 6AS exerted at the same time strong effect on plant height and FHB resistance. The QTL on 4AL mapped to a similar region as a QTL associated with PH in hexaploid wheat corresponding to a kaurenoic acid oxidase (KAO) gene (Khlestkina et al 2010; Zanke et al 2014), while reduced height genes have been reported on 6AS in durum wheat (Haque et al 2011). These genes are gibberellin-sensitive and not comparable to Rht - B1 in that aspect.…”
Section: Discussionmentioning
confidence: 99%